2013
DOI: 10.3109/02699052.2013.823659
|View full text |Cite
|
Sign up to set email alerts
|

Moderate–severe traumatic brain injury causes delayed loss of white matter integrity: Evidence of fornix deterioration in the chronic stage of injury

Abstract: These data contribute to the growing body of evidence that loss of white matter continues in moderate and severe TBI even after the acute neurological effects of TBI have resolved. As the fornix plays a critical role in memory, this may be a contributing factor to the poor clinical outcomes observed in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 49 publications
3
41
0
Order By: Relevance
“…Similar to animal data showing a temporal progression of axonal injury, measured as changes of DTI parameters (Mac Donald et al, 2007a), clinical studies of TBI patients at different stages also report different DTI findings, suggesting a temporal progress of TBI pathology. Adnan et al (2013) prospectively scanned 29 moderate to severe TBI patients at two time points: 5 months and 29 months after injury. Adnan et al (2013) prospectively scanned 29 moderate to severe TBI patients at two time points: 5 months and 29 months after injury.…”
Section: Temporal Progression Of Dti Signature In Tbi Patientsmentioning
confidence: 99%
“…Similar to animal data showing a temporal progression of axonal injury, measured as changes of DTI parameters (Mac Donald et al, 2007a), clinical studies of TBI patients at different stages also report different DTI findings, suggesting a temporal progress of TBI pathology. Adnan et al (2013) prospectively scanned 29 moderate to severe TBI patients at two time points: 5 months and 29 months after injury. Adnan et al (2013) prospectively scanned 29 moderate to severe TBI patients at two time points: 5 months and 29 months after injury.…”
Section: Temporal Progression Of Dti Signature In Tbi Patientsmentioning
confidence: 99%
“…Moreover, one must distinguish clinically and pathologically between static, non-progressive cumulative effects of multiple concussions vs. progressive findings of symptomatic neurodegenerative disease. Complicating the situation are cases of a single, but more serious TBI associated with increased risk of dementia (Blennow et al, 2012; Sayed et al, 2013) as well as atrophy and loss of white matter integrity in the sub-acute and chronic stages of injury (Greenberg et al, 2008; Ng et al, 2008; Whitwell and Josephs, 2011; Adnan et al, 2013)…”
Section: Summary and Conclusion: Much Remains To Be Knownmentioning
confidence: 99%
“…Evidence is accumulating from several laboratories including our own that following early cognitive recovery, many patients show statistically and clinically significant cognitive decline in the ensuing months (Ruff et al, 1991) and years (Millis et al, 2001; Till et al, 2008). We and others have also demonstrated that the brain's structure is not static after resolution of acute injuries, with TBI patients showing volume loss and reduced white matter (WM) integrity during the sub-acute and chronic stages of injury (Bendlin et al, 2008; Greenberg et al, 2008; Ng et al, 2008; Sidaros et al, 2009; Farbota et al, 2012; Adnan et al, 2013). Given that such atrophy is observed in some studies well after the resolution of acute events (Greenberg et al, 2008; Ng et al, 2008; Ross et al, 2012), and that sub-acute structural deterioration has been correlated with functional and behavioral outcomes (Bendlin et al, 2008; Sidaros et al, 2009), these changes cannot be attributed simply to encephalomalacia (i.e., scar formation associated with gliosis) or to resolution of edema.…”
Section: Introductionmentioning
confidence: 96%